2021
DOI: 10.3390/w13243632
|View full text |Cite
|
Sign up to set email alerts
|

Using Geochemical Fingerprints for Assessing Sediment Source Apportionment in an Agricultural Catchment in Central Argentina

Abstract: In the hilly semi-arid region of central Argentina, where the agricultural frontier expands at the expense of natural ecosystems, soil erosion is one of the most alarming environmental problems. Thus, obtaining knowledge about the dynamics of erosive processes and identifying erosion hotspots constitutes a primary scientific objective. This investigation is focused on estimating the apportionments of main sources of sediments, at the mouth of a small catchment called Durazno del Medio, located in the province … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…Assuming high mining activities in those areas, these results agree with the findings by Fang and Fan [76], who investigated sediment sources in the Shouchang watershed (southeastern China), concluding that most sediments were originated from human activities. Similarly, one of the main sediment sources found by Garcias et al [77] in Argentina was exotic forest plantations, normally characterized for yielding sediments after clearcutting and road construction, e.g., [78,79], while Tiecher et al [80] concluded that agricultural fields in Brazil are a significant source of sediments, even under no-tillage conditions, similar to the findings by Zhang et al [81] in Hampshire, UK. However, Liu et al [82] reported that agriculture represented less than 10% of sediment sources in the Lower Little Bow River (Alberta), with the majority of sources unknown.…”
Section: Global Perspectivessupporting
confidence: 56%
“…Assuming high mining activities in those areas, these results agree with the findings by Fang and Fan [76], who investigated sediment sources in the Shouchang watershed (southeastern China), concluding that most sediments were originated from human activities. Similarly, one of the main sediment sources found by Garcias et al [77] in Argentina was exotic forest plantations, normally characterized for yielding sediments after clearcutting and road construction, e.g., [78,79], while Tiecher et al [80] concluded that agricultural fields in Brazil are a significant source of sediments, even under no-tillage conditions, similar to the findings by Zhang et al [81] in Hampshire, UK. However, Liu et al [82] reported that agriculture represented less than 10% of sediment sources in the Lower Little Bow River (Alberta), with the majority of sources unknown.…”
Section: Global Perspectivessupporting
confidence: 56%